2009 IEEE 20th International Symposium on Personal, Indoor and Mobile Radio Communications 2009
DOI: 10.1109/pimrc.2009.5450324
|View full text |Cite
|
Sign up to set email alerts
|

Transmit power allocation for self-organising future cellular mobile radio networks

Abstract: Future mobile radio networks are expected to witness an increase in capacity demand. Since the spectrum suited for mobile radio application is scarce, the spectrum efficiency of future mobile radio networks has to be increased in order to be able to meet the capacity demand. In networks applying adaptive modulation and coding, both, transmit power and bandwidth can be considered as resources. In order to achieve high spectrum efficiency, the adaptation of the allocation of transmit power and bandwidth to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Furthermore, it is clear that the average throughput of fuzzy logic is improved over the greedy heuristic (by 4%), even though after 15 time slots the performance is similar. This highlights that fuzzy logic ICIC is optimal on a cell-individual basis, however is able to (due to other inputs such as rate requirement and desired signal strength) converge to this optimum much quicker 6 .…”
Section: Results Comparisonmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is clear that the average throughput of fuzzy logic is improved over the greedy heuristic (by 4%), even though after 15 time slots the performance is similar. This highlights that fuzzy logic ICIC is optimal on a cell-individual basis, however is able to (due to other inputs such as rate requirement and desired signal strength) converge to this optimum much quicker 6 .…”
Section: Results Comparisonmentioning
confidence: 99%
“…efficiency is achieved quite rapidly. The added energy efficiency due to LA is a direct result of the augmented throughputs (see (6)). It is shown that ABS transmission is slightly more energy efficient than maximum power transmission, which is logical since on average 10% less power is used, but the loss in throughput is <10%, thus enhancing the energy efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A convex optimization technique has been proposed in [9] to adjust the allocation of transmit power to the cells in order to adapt the network to changing capacity demands. The bandwidth allocated to the cells is fixed, but the transmit power allocated to the cells is adjusted in order to adapt the capacities of the cells according to the demand.…”
mentioning
confidence: 99%